Low frequency noise measurement and analysis of capacitive micro-accelerometers: Temperature effect - Mohd Yasin, Faisal; Nagel, David J.; Ong, D. S.; Korman, Can E.; Chuah, Hean Teik (2007)
In this work, a noise measurement of capacitive micro-accelerometers incorporating temperature effect is presented. In the setup, a hot plate is used to heat the device up to temperatures in the 75 degree C range. A thermo couple attached to the enclosure is used to assess its temperature. The data show that the noise power increases at high temperature, but not as significant as predicted by the theory.